2022
DOI: 10.1101/2022.05.27.493609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

G1-Cyclin2 (Cln2) promotes chromosome hypercondensation in eco1/ctf7 rad61 null cells during hyperthermic stress in Saccharomyces cerevisiae

Abstract: Eco1/Ctf7 is a highly conserved acetyltransferase that activates cohesin complexes and is critical for sister chromatid cohesion, chromosome condensation, DNA damage repair, nucleolar integrity, and gene transcription. Mutations in the human homolog of ECO1 (ESCO2/EFO2), or in genes that encode cohesin subunits, result in severe developmental abnormalities and intellectual disabilities referred to as Roberts Syndrome (RBS) and Cornelia de Lange Syndrome (CdLS), respectively. In yeast, deletion of ECO1 results … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 151 publications
0
8
0
Order By: Relevance
“…Defects in cohesin regulation are also tightly correlated with several forms of cancer (80)(81)(82). Despite the importance of cohesin functions, little is known regarding the regulation of cohesins early during the cell cycle, but recent findings confirm that MCD1 expression may be a critical component (83,84). In this study, we identify FDO1 as a novel regulator of MCD1 expression.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Defects in cohesin regulation are also tightly correlated with several forms of cancer (80)(81)(82). Despite the importance of cohesin functions, little is known regarding the regulation of cohesins early during the cell cycle, but recent findings confirm that MCD1 expression may be a critical component (83,84). In this study, we identify FDO1 as a novel regulator of MCD1 expression.…”
Section: Introductionmentioning
confidence: 74%
“…Eco1 (which is essential only during S phase) and Pds5 (an auxiliary cohesin subunit required for cohesion from S phase to anaphase onset) support cohesin functions through independent mechanisms (35,41,42,53). In a remarkable convergence of studies, however, deletion of CLN2 was found to promote the viability of both eco1Δ rad61Δ at 37°C and pds5 elg1 cells (83,84). The latter study provided evidence that CLN2 deletion increased Mcd1 levels, such that simply elevating Mcd1 protein levels was sufficient to render viable pds5 elg1 double mutant cells (83).…”
Section: Reduced Mcd1 Levels Are Responsible For Eco1δ Rad61δ Double ...mentioning
confidence: 99%
See 3 more Smart Citations